Dietary nitrate supplementation augments nitric oxide synthase-dependent and independent reflex cutaneous vasodilation in healthy humans - Levitt, Erica L. (Kansas State University, 2013)
Beetroot juice (BRJ) has been shown to increase NO-dependent dilation through both NOS-dependent and NOS-independent pathways. We hypothesized BRJ supplementation would augment reflex cutaneous active vasodilation. Subjects were equipped with two microdialysis fibers on the forearm and randomly assigned as control (Ringer’s) or NOS inhibition (20mM L-NAME). Whole-body heating was achieved via water-perfused suits to raise core temperature (Tc; ingestible telemetric pill) 0.8°C. Maximal cutaneous vasodilation was reached by administering 54mM SNP and local heating to 43°C. Skin blood flow was measured via laser-Doppler flowmetry and mean arterial pressure determined; cutaneous vascular conductance (CVC) was calculated and expressed as %CVCmax. Subjects underwent heat stress pre- and post-nitrate supplementation (3 days of BRJ: 5mM, 0.45g nitrates per day). BRJ increased the plateau CVC at control (pre: 57 ± 3 vs. post: 80 ± 5 %CVCmax) and L-NAME (pre: 36 ± 3 vs. post: 52 ± 6 %CVCmax; p<0.05 for all conditions) sites. The %NO contribution increased from pre- to post-BRJ (pre: 44 ± 5 %CVCmax vs. post: 64 ± 6 %CVCmax; p<0.05). These data suggest that BRJ augments the NOS-dependent and NOS-independent component of reflex cutaneous vasodilation.
Keywords: Dietary Nitrates; Reflex cutaneous vasodilation; NOS-dependent vasodilation; NOS-independent vasodilation; Kinesiology (0575)